The Christianization of Interest - Moehlman, Conrad Henry (Church history, 1934)
In his economic history of the Schwarzwald, published in 1891, Eberhard Gothein called attention to the connection between Calvinism and modern capitalism.Thirteen years later, in a series of brilliant essays, Max Weber insisted that Calvinism and capitalism were intimately related and alluded to such Calvinistic virtues as secular asceticism, thrift, and predestination as significant elements in the situation.2